Low temperature stabilization of nanoscale epitaxial spinel ferrite thin films by atomic layer deposition - Coll, Mariona; Moreno, Josep M. Montero; Gazquez, Jaume; Nielsch, Kornelius; Obradors, Xavier; Puig, Teresa (Advanced Functional Materials, 2014)
In this work heteroepitaxial stabilization with nanoscale control of the magnetic Co2FeO4 phase at 250 C is reported. Ultrasmooth and pure Co2FeO4 thin films (5-25 nm) with no phase segregation are obtained on perovskite SrTiO3 single crystal (100) and (110) oriented substrates by atomic layer deposition (ALD). High resolution structural and chemical analyses confirm the formation of the Co-rich spinel metastable phase. The magneto-crystalline anisotropy of the Co2FeO4 phase is not modified by stress anisotropy because the films are fully relaxed. Additionally, high coervice fields, 15 kOe, and high saturation of magnetization, 3.3 μB per formula unit (at 10 K), are preserved down to 10 nm. Therefore, the properties of the ALD-Co2FeO4 films offer many possibilities for future applications in sensors, actuators, microelectronics, and spintronics. In addition, these results are promising for the use of ALD compared to the existing thin-film deposition techniques to stabilize epitaxial multicomponent materials with nanoscale control on a wide variety of substrates for which the processing temperature is a major drawback.
CRIS-Team Scopus Importer:2023-03-20
Keywords: atomic layer deposition; epitaxy; spinel ferrites; stability; thin films